SOCIO-ECONOMIC CHARACTERISTICS OF SHEEP AND GOATS TRADERS IN BAUCHI STATE, NIGERIA - Kolo, A.; Jibril, S. A.; Sani, M. H.; Mohammed, I. (Journal of Agripreneurship and Sustainable Development, 2019)
The study analyzed socio-economic characteristics of sheep and goats traders in Bauchi State, Nigeria. Multi-stage sampling technique was used to select 321 sheep traders and 220 goats’ traders. Data were collected with aid of structured questionnaire and analyzed using descriptive statistics and inferential statistics (mean score) were employed for the study. The result revealed that marketing of sheep and goats was dominated by married men with non-formal education and had marketing experience of 14 years to 18 years. However, the mean household size of sheep and goats traders was 9 persons and 7 persons, respectively. The mean current capital level of sheep and goats traders was N93,231.58 and N67,927.02, respectively. This shows that both sheep and goat’s traders in the study area were small scale traders. The result further discloses that, 51.40% and 47.73% of sheep and goats traders sourced their capital through personal savings, which are non-institutional credit sources. Inadequate capital (1st), poor access to formal credit (2nd), lack of standard unit of measurement (3rd), lack of cooperative/association (4th), disease and physical risk (5th) as well as seasonality of demand and supply (6th) were the major constraints associated with marketing sheep and goats in the study area. The study concludes that socio-economic characteristics of traders play an important role in marketing of sheep and goats in the study area, which will also have effects on the level of profit margin. The study recommends that traders should improve their level of education. This should be seen as a step option for combating illiteracy among traders in the study area. Provision of mini credit facilities to the traders, formation of sheep and goats traders association or cooperatives should be given serious consideration so as to improve the effectiveness of sheep and goats marketing in the study area.